The Dg RES generation, storage, utilization and integration program ’1 village – 1 MW’ of the Bükk-Miskolc Region, Phase 1–3. - Nagy, József; Sinyei, Marianna; Vass, Lajos (Acta Agraria Debreceniensis, 2012)
The usage of renewable energy sources (RES) and the increase of energy efficiency could be the solution for the difficulties of the rural impoverished inhabitants. A rural development company with the support of the communities designs the development resources from the EU and the Hungarian State for RES generation and organizes the ’1 village – 1 MW’ RES generation, storage, distribution and usage integration.